THE REPRESENTATION OF CRIMINAL PSYCHOLOGY IN CONTEMPORARY DETECTIVE FICTION - Fayzullayeva Nigina Surat kizi (International Journal of Literature and Language Studies, 2026)
Contemporary detective fiction has undergone significant transformation in recent decades, shifting its focus from the mere investigation of crimes to the psychological exploration of criminals and their motivations. Modern detective novels increasingly emphasize the inner world of offenders, presenting crime as a result of complex psychological, social, and emotional factors rather than as a simple violation of legal norms. This article examines the representation of criminal psychology in contemporary detective fiction and analyzes the narrative techniques employed by authors to portray criminal behavior. Using qualitative textual analysis, the study explores selected contemporary detective novels and identifies key patterns in the depiction of criminal minds. The findings reveal that contemporary detective fiction relies heavily on psychological realism, trauma-based characterization, and multifaceted narrative structures to create credible and compelling criminal characters. Such representations contribute to a deeper understanding of human behavior and demonstrate the growing importance of psychological analysis within the detective genre.